PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI CAFE DONGENG THERACE GARUT - Gunawan, Zahran; Hermina, Tinneke; Rizki Gumelar, Irfan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of product quality and location on purchasing decisions at Cafe Dongeng Therace Garut. The background of this study is based on the significant growth of the culinary sector in Indonesia, including in Garut Regency, accompanied by an 18% increase in the number of cafes over the past three years. Cafe Dongeng Therace faces fluctuations in visitor numbers and customer complaints regarding taste consistency and limited parking facilities. This study employs a quantitative approach using a survey method with 150 respondents, analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that product quality and location have a positive and significant influence on purchasing decisions, both partially and simultaneously. These findings emphasize the importance of managing product quality and implementing appropriate location strategies to enhance the competitiveness of culinary businesses.